Current Productions Carnuntum, German Limes and Radiopast - F. Humer; C. Gugl; M. Pregesbauer; F. Vermeulen; Ch. Corsi; M. Klein (Virtual Archaeology Review)
The here presented three chosen projects mark out different techniques of production and their transmission of content. The differentiated impact on the public absorption of the transported content are described dependent to experiences with it in exhibitions and publications, and can be used to rectify future approaches of similar topics. In most of these productions, technical difficulties were observed and solved through extensive use of different tools and techniques to achieve a reasonable output and represent our current state of knowledge which we would like to share. The documentation of the production as well as the communication between the production and research team is indispensable to the sucsess of these media formats.